Determinan Pengangguran ASEAN era MEA - Regitha Adjeng Pramesty; Rahayu Kistanti, Nurjannah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The ASEAN Economic Community is a form of globalization occurring within ASEAN. Macroeconomic issues such as unemployment present a challenge for ASEAN countries as they strive to succeed in reducing unemployment rates through investment, trade in goods and services, connectivity, and labor management. This research aims to analyze the influence of economic growth, FDI, economic globalization, social globalization and political globalization on unemployment in member countries of the ASEAN Economic Community. This research is quantitative research using panel data during the 2016-2022 period with observations from ten member countries of the ASEAN Economic Community. The analysis method used is panel data regression. Based on the results of the panel data regression model selection test using the Hausman test, the Fixed Effect Model (FEM) was the appropriate model to be used in this research. The research results show that the economic growth variable has a negative and significant effect on unemployment with a coefficient of -0.039169. The FDI variable has a positive and significant effect on unemployment with a coefficient of 0.123884. The political globalization variable has a negative but not significant effect on unemployment with a coefficient of -0.176722. The economic globalization variable has a positive and significant effect on unemployment with a coefficient of 0.157475. The social globalization variable has a negative and significant effect on unemployment with a coefficient of -0.308238..